2006
DOI: 10.1042/ba20060027
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of flatus‐inducing factors in soymilk by immobilized α‐galactosidase

Abstract: Alpha-galactosidase from Aspergillus oryzae was immobilized on chitosan beads using glutaraldehyde as a cross-linking agent. The general properties of free and immobilized enzymes were determined. The optimum pH for the free and immobilized enzymes was 4.8 and 4.6 respectively. The optimum temperature for the free enzyme was 50 degrees C, whereas that of immobilized enzyme was increased to 56 degrees C. Kinetic parameters were determined with synthetic substrate (p-nitrophenyl alpha-D-galactopyranoside) and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…α-galactosidase (Kotwal et al 1999). In case of Aspergillus oryzae and Aspergillus niger , both of them showed K m of 5.5 mM for raffinose (Kulkarni et al 2006), while in case of Humicola sp., it was 1.45 mM for raffinose (Kotwal et al 1999). This study revealed that our enzyme has high affinity for synthetic substrate than natural substrate raffinose which is a larger and more bulky trisaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…α-galactosidase (Kotwal et al 1999). In case of Aspergillus oryzae and Aspergillus niger , both of them showed K m of 5.5 mM for raffinose (Kulkarni et al 2006), while in case of Humicola sp., it was 1.45 mM for raffinose (Kotwal et al 1999). This study revealed that our enzyme has high affinity for synthetic substrate than natural substrate raffinose which is a larger and more bulky trisaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some debate about the potential health benefits of non-digestible oligosaccharides ( Delzenne and Roberfroid, 1994 ; Roberfroid, 2002 ), various physico-mechanical treatments and breeding programs have been reported to reduce RFO concentrations in seeds ( Aguilera et al, 2009 ; Devindra et al, 2011 ). Even the enzymatic removal of RFOs from seed-derived products ( Kulkarni et al, 2006 ; Patil et al, 2009 ) using immobilized α-galactosidase from Aspergillus oryzae , has been extensively studied ( Slominski et al, 1994 ; Khalil and Mansour, 1998 ; Feng et al, 2008 ; Liu et al, 2014 ). To improve nutritional quality of leguminous seeds, RFO concentrations need to be reduced ( Qiu et al, 2015 ) without affecting their role during seed development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fermentation allows people with gastrointestinal problems to consume foods that cause bloating. The ability of microorganisms to synthesize the enzyme β-glucosidase allows the hydrolysis of soybean oligosaccharides, thereby reducing the risk of flatulence commonly occurring after the consumption of legumes and their products [ 139 ]. That feature may be used to enrich the menu of people on an elimination diet.…”
Section: Health Effects Of Fermented Vegetablesmentioning
confidence: 99%